The Cyber Threat Landscape in South Africa: A 10-Year Review - Pieterse, Heloise (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2021)
The world is witnessing a rise in cyber-related incidents. As information technology improves and the reliance on technology increases, the frequency and severity of cyber incidents escalate. The impact is felt globally, and South Africa is not immune to the effects. The country’s fast-paced technological evolution continues to increase the attack surface within the cyber domain. The increased attack surface is confirmed by recent cyberattacks affecting well-known and established South African organisations. This article reviews findings from an evaluation of South Africa’s cyber threat landscape that analysed 74 cyber incidents identified as occurring between 2010 and 2020. The 74 incidents are categorised according to incident type, affected sector, perpetrator type, and motivation. It is found that the most common incident type is data exposure, the most-affected sector is the public sector, the most prevalent perpetrators are hackers, and the most common motivation is criminal. The article makes recommendations about how South Africa can reduce the risk factors in its cyber threat landscape.
Keywords: cybersecurity, cyber threats, cyberattacks, cyber incidents, attack surface, compromised websites, cybercrime, data exposure, system intrusion, denial of service